Ferrari ki sawaari [smal guys big Dreams] - Pritam 1971- (Mumbai, 2012)
A little boy thinks of nothing but cricket. His father, Rusy, thinks of nothing but his little boy. To fulfil his son's dream of playing at Lord's cricket ground, the honest and upright Rusy takes a reckless step. He borrows a gleaming red Ferrari, just for one hour. The only trouble: he doesn't inform the car's legendary owner